Three Dimensional Analysis Method and Application of Pressure Drop after Coal Seam Pressure. Issue 1 (November 2020) - Peng, Hongzhao; Kang, Yunwei; Zeng, Wenting; Sun, Bin; Chen, Dong
Abstract: The analysis of pressure drop after compression is very important for obtaining coalbed gas reservoir parameters and optimizing coalbed gas fracturing design. However, there are some problems such as closed pressure analysis, inaccurate calculation of fracture geometry and effective permeability. In this paper, a three-dimensional analysis model of post-pressure pressure drop is established based on the principle of fluid volume balance during injection and closure. Based on the quasi-three-dimensional fracture model, the geometric size, fitting pressure and filtration coefficient of fracturing fluid are explained, and the practicability and accuracy of this method in the analysis of pressure drop after coal seam pressure are verified by field construction examples.